2022
DOI: 10.1038/s41598-022-21388-w
|View full text |Cite
|
Sign up to set email alerts
|

A pro-oxidant combination of resveratrol and copper down-regulates multiple biological hallmarks of ageing and neurodegeneration in mice

Abstract: Billions of cells die in the body every day, and cell-free chromatin particles (cfChPs) which are released from them enter into the extracellular compartments of the body, including into the circulation. cfChPs are known to readily enter into healthy cells to damage their DNA and activate apoptotic and inflammatory pathways. We have hypothesized that lifelong assault on healthy cells by cfChPs is the underlying cause of ageing, and that ageing could be retarded by deactivating extra-cellular cfChPs. The latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…Resveratrol-copper and its mechanism of action Of the three deactivating agents for cfChPs that have been previously utilised in preclinical studies, namely, CNPs, DNAse I, and R-Cu, the latter has been proven to be the agent of choice for therapeutic use in humans [21]. This is primarily because R-Cu can be easily administered orally and has demonstrated little toxicity in preclinical and clinical studies, even after prolonged administration [22]. Resveratrol (R) is a nutraceutical that has been extensively studied because of its antioxidant properties [23].…”
Section: The Chemotoxicity Enigmamentioning
confidence: 99%
“…Resveratrol-copper and its mechanism of action Of the three deactivating agents for cfChPs that have been previously utilised in preclinical studies, namely, CNPs, DNAse I, and R-Cu, the latter has been proven to be the agent of choice for therapeutic use in humans [21]. This is primarily because R-Cu can be easily administered orally and has demonstrated little toxicity in preclinical and clinical studies, even after prolonged administration [22]. Resveratrol (R) is a nutraceutical that has been extensively studied because of its antioxidant properties [23].…”
Section: The Chemotoxicity Enigmamentioning
confidence: 99%
“…However, compelling recent evidence indicates that ageing is the result of the lifetime damaging effects of cfChPs on healthy cells which can be ameliorated by ROS generated by the administration of R-Cu. It has been recently reported that the prolonged oral administration of R-Cu can downregulate multiple biological hallmarks of ageing in brain cells of C57Bl/6 mice, including telomere shortening, amyloid deposition, apoptosis, inflammation, mitochondrial dysfunction, DNA damage, senescence, and aneuploidy ( Figure 2 ; Pal et al, 2022 ). In the same study, R-Cu administration was also associated with significant reductions in the levels of serum glucose, cholesterol, and C-reactive protein ( Pal et al, 2022 ).…”
Section: R-cu Treatment Retards Ageing and Neurodegenerationmentioning
confidence: 99%
“…It has been recently reported that the prolonged oral administration of R-Cu can downregulate multiple biological hallmarks of ageing in brain cells of C57Bl/6 mice, including telomere shortening, amyloid deposition, apoptosis, inflammation, mitochondrial dysfunction, DNA damage, senescence, and aneuploidy ( Figure 2 ; Pal et al, 2022 ). In the same study, R-Cu administration was also associated with significant reductions in the levels of serum glucose, cholesterol, and C-reactive protein ( Pal et al, 2022 ). An interesting observation was the differential effects of R-Cu between male and female mice on telomere shortening, which requires further study ( Pal et al, 2022 ).…”
Section: R-cu Treatment Retards Ageing and Neurodegenerationmentioning
confidence: 99%
“…In human lung fibroblasts, Cu induced SA-β-Gal expression and altered proteostasis [ 187 ]. Interestingly enough, treatment of Cu with the drug resveratrol decreased the expression of p16 INK4a in the brains of aged mice, as well as several other hallmarks of brain aging, suggesting a non-monotonic response to Cu in brain aging [ 200 ]. While there is strong evidence of Cu inducing senescence in cell culture, a potential anti-aging property of Cu highlights the knowledge gaps that exist for metals toxicity, cellular senescence, and aging.…”
Section: Heavy Metals Induce Cellular Senescencementioning
confidence: 99%